Complications of XEN gel stent implantation for the treatment of glaucoma: a systematic review - Gan, Lu; Wang, Lixiang; Chen, Jun; Tang, Li (Frontiers in Medicine, 2024)
The only confirmed modifiable glaucoma risk factor is elevated intraocular pressure (IOP).XEN gel stent (Allergan Plc, Dublin, Ireland) implantation is an example of MIGS that have been used to treat different types of glaucoma.2. The advantages of XEN Gel stent implantation include the minimally invasive ab interno/ab externo access, sparing of the sclera and conjunctiva, better preservation of corneal endothelium, obviating the need for iridectomy and sutures, and a shorter surgery time.What is new： 1.Suprachoroidal space hemorrhage, endophthalmitis, and malignant glaucoma are potentially sight-threatening but rare complications of XEN gel stent implantation, which required special caution of the surgeon.2.Especially for rare complications, the experience of diagnosis, prevention, management, and prognosis is quite limited and no expert consensus or guideline is available.3.Our systematic review as the first comprehensive summary of perioperative complications associated with XEN gel stent implantation demonstrates both common and rare complications and their incidence, mechanisms, and management methods.